IBN AL-HAYTHAM, IBN SĪNĀ, AL-ṬŪSĪ : ÉGALITÉ OU CONGRUENCE. Issue 2 (September 2019) - Rashed, Roshdi
Abstract: As their greek predecessors, mathematicians and arab-speaking philosophers raised several important epistemological questions. One of those questions concerns the concept of equality and the concept of congruence of geometric magnitudes. What was the meaning of such concepts? How were they related to the idea of movement? Answers to these questions were often combining metric elements and other, philosophical (topological) elements, and I chose to study those of a mathematician, of a philosopher, and of a mathematician-philosopher. Résumé: Les mathématiciens et les philosophes arabophones, comme leurs prédécesseurs grecs, ont soulevé plusieurs questions épistémologiques fondamentales. Parmi ces questions figure celle qui porte sur le concept d'égalité et sur celui de congruence des grandeurs géométriques. Mais qu'entendait-on par de tels concepts ? quelle était leur relation à l'idée de mouvement ? Comme les réponses à ces questions combinaient souvent des éléments métriques et d'autres, philosophiques (topologiques), j'ai choisi d'étudier celles d'un mathématicien, d'un philosophe et d'un mathématicien-philosophe.